Ice Phenology of Lakes in the Byers, Keller, and Fildes Peninsulas, Maritime Antarctica, from 2014 to 2023 using SAR Data - Viel, Jorge Antônio; Rosa, Kátia Kellem da; Petsch, Carina; Velho, Luiz Felipe; Soffiatti, Danielle Dall Amaria; Aita, Federico; Vieira, Rosemary (Revista Brasileira de Geomorfologia, 2026)
This study examined the ice phenology of twenty-five lakes located in the Fildes and Keller peninsulas (King George Island) and the Byers Peninsula Livingston Island), Antarctica, using SAR (Sentinel-1) data from 2014 to 2023. A backscatter threshold was established for ice-free and frozen surfaces in S1 images. The temporal analysis of lake phenology was conducted covering the months from October to March. The slope context, altitude, and distance from the coast of the lakes were characterized. Field activities were carried out to validation. Temporal backscatter analysis revealed seasonal patterns of lake surface freezing and thawing, which were correlated with climatic variables, including mean air temperature, precipitation, and wind. Mean air temperature emerged as the primary driver of ice cover variability, with fewer frozen days observed in years of increased positive temperatures, particularly during El Niño events. The years 2015 and 2019 exhibited less thawing, while 2023 recorded the lowest extent of frozen lake surfaces (99.15%). Local factors, including wind speed and direction, and coast distance and altitude, also influenced the observed patterns. Sentinel-1 imagery proved effective for mapping and monitoring lake surface ice cover in glacial and periglacial environments, underscoring its potential for assessing lacustrine responses to climate variability.